Catalytic Asymmetric Electrophilic Amination Reactions To Form Nitrogen-Bearing Tetrasubstituted Carbon Stereocenters - Zhou, Feng; Liao, Fu-Min; Yu, Jin-Sheng; Zhou, Jian (Synthesis, 2014)
The catalytic asymmetric electrophilic amination has been established as a fruitful methodology for the construction of nitrogen-bearing tetrasubstituted carbon stereocenters, with its roots nourished by the latest achievements in chiral catalysis and synthetic strategies. This review summarizes the recent progresses, briefly discusses the reaction mechanism and challenges in this context, and outlines synthetic opportunities for future development.1 Introduction2 Transformations Based on Azodicarboxylates2.1 α-Substituted Prochiral Aldehydes and Ketones2.2 Ketenes2.3 Doubly Activated Dicarbonyl Compounds2.4 Heteroatom-Containing Activated Methines2.5 Heterocyclic Nucleophiles3 Amination Reactions Using other Amination Reagents4 Conclusion
Keywords: amination; asymmetric catalysis; tetrasubstituted carbon; stereogenic center; Lewis acid catalysis; organocatalysis